PENGARUH FINANCIAL TARGET, KETIDAKEFEKTIFAN PENGAWASAN, PERUBAHAN AUDITOR, PERUBAHAN DIREKSI DAN AROGANSI TERHADAP KECURANGAN LAPORAN KEUANGAN DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI - Stefanus Heru Santoso (Jurnal Magister Akuntansi Trisakti, 2019)
AbstractThe purpose of this research is to analyze the effects of financial targets, ineffective monitoring, change in auditor, change in directors and arrogance on financial statement fraud with audit commitee as moderating variabel in  basic industry and chemicals, miscellaneous industry and consumer goods industry sector Companies listed on Indonesia Stock Exchange for period 2015-2017. The method used in this research is hypothesis testing. The data collecting method using secondary data type in the form of annual report of basic industry and chemicals, miscellaneous industry and consumer goods industry sector Companies listed on Indonesia Stock Exchange for period 2015-2017. The data analysis technique is Moderated Regression Analysis (MRA). The research result shows that financial target, change in auditor and arrogance have positive effect on financial statement fraud of basic industry and chemicals, miscellaneous industry and consumer goods industry sector Companies listed on BEI. Meanwhile, ineffective monitoring and change in directors have no positive effect on financial statement fraud of basic industry and chemicals, miscellaneous industry and consumer goods industry sector Companies listed on BEI. The result also shows that the audit commitee as the moderating variable have a weakening impact to the relationship between financial target and change in auditor on financial statement fraud, while the audit commitee as the moderating variable have no an impact of weakening between ineffective monitoring, change in directors and arrogance on financial statement fraud.